Animation VR Motion Simulation Evaluation Based on Somatosensory Simulation Control Algorithm - Yang, Zirui (Informatica, 2024)
With the continuous development of social economy, the animation industry has been continuously improved, and has become a necessity for people's daily important activities. Meanwhile, VR sports realizes the simulation of various actions, such as indoor tennis, realistic somatosensory games and so on. But how to ensure the authenticity and experience of animation VR sports is extremely important. The somatosensory simulation control algorithm is introduced to sort out the business flow of animation VR sports in this paper. Unlike the traditional simulation method, the somatosensory simulation control integrates the perception of the vestibule, provides extremely rapid feedback on the output error, realizes the continuous correction and prediction of the input angular velocity and the corresponding acceleration, so as to realize the prediction of undulations of the terrain in the animation VR movement. The simulation experiment results show that the somatosensory simulation control algorithm is effective and can support the phase delay to improve the consistency of the corresponding animation VR motion simulation.